Marketing Analysis of the Stamped Batik Industry to Enhance Worker’s Income in Purwokerto - Lestari, Purwati Budi (CV. Tripe Konsultan, 2025)
The stamped batik industry in Purwokerto is a cultural heritage with strategic economic value in creating jobs and supporting the local economy. This study aimed to analyze the marketing strategy of the stamped batik industry and its impact on increasing labor income in Purwokerto City. The research method employed was a qualitative approach, utilizing a case study, which involved 50 informants comprising MSME owners, workers, consumers, local government officials, and academics. Data were collected through in-depth interviews, field observations, and documentation studies, then analyzed using the Miles and Huberman interactive analysis model. The research results indicate that the stamped batik industry in Purwokerto comprises 47 UMKM, employing a total of 380 workers and generating a monthly production value of IDR 1.2 billion. The marketing strategies implemented include digital marketing (68% of UMKM), product diversification, and local brand development. The social media platforms Instagram (85%), Facebook (72%), and marketplaces (45%) are the main digital marketing channels. The implementation of marketing strategies has proven effective in increasing production volume by 35% and product sales value by 25-40%, which has a positive impact on increasing labor income through increased working hours, bonuses, and job stability. Supporting factors for industry development include government support, the availability of skilled human resources, adequate digital infrastructure, and a strong local culture. Meanwhile, the main inhibiting factors are limited capital, the quality of digital marketing human resources that still needs to be improved, competition with batik products from other regions, and dependence on imported raw materials. This study recommends improving the digital marketing capabilities of UMKM, providing continued government support in training and access to capital, and developing workforce skills in marketing and business management to create a sustainable business model for the Purwokerto stamped batik industry.